Assessment of old timber members: Importance of wood species identification and direct tensile test information. (20th May 2019) - Machado, José Saporiti; Pereira, Filipe; Quilhó, Teresa
Highlights: Wood species identification is crucial for a proper evaluation of timber members. Semi-destructive test provide information regarding possible aging effects. The effect of ageing (damage of cell wall) lead to a reduction of tensile strength. In-situ test information should be crossed with wood species information. Abstract: A proper assessment of the properties of timber members is dependent upon the capacity for acquiring sufficient information onsite. A large part of this depends on the ability to identify wood species which is consequently used for selecting and applying a suitable visual strength grading standard. However, given the wide variability associated with the mechanical properties, normally above 20%, and the possible ageing effects due to load and moisture history, visual grade information should be complemented by information from onsite tests. This paper presents the results of a methodology for assessing old timber members where all information collected from wood identification and semi-destructive testing (wood coring and tensile tests) are combined and analysed. The results stress the importance that the combination of information from different sources can provide in terms of a safer and more reliable assessment of timber members in service.